Implementation of Range of Motion Exercises to Improve Muscle Strength in Ischemic Stroke Patients in the Flamboyan Ward at Banjar General Hospital - Indriani, Novi; Rahmawati Putri , Tari (Jurnal Kesehatan Mahardika, 2024)
Stroke is a decrease in blood circulation to the brain that causes focal and global neurological deficits that can become severe for 24 hours after the first appearance or more and can cause death. The incidence of stroke in the world is 13.7 million (2020), Indonesia has 731,783 cases or 10.9% (2018), West Java has 52,511 cases or 11.4%, and Banjar City has 9.03%. The purpose of this scientific paper is to describe nursing care in stroke patients who are given range of motion exercises. The method used in this scientific paper is combined (qualitative and quantitative). Both respondents were given the implementation of ROM exercises for 5 days. Respondent 1 on the first day of muscle strength of the right hand and foot was 5 while the left was 3,and on the fifth days, the left hand was from 3 to 4. Respondent 2 on the first day of left hand and foot muscle strength was 5 while right 3, and day five, right leg and hand from 3 to 4. The conclusion that can be drawn is that range of motion exercises are effective for increasing muscle strength in stroke.